2016
DOI: 10.1016/j.msec.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant tissue response and biodegradation performance of a Mg–1.0Ca–0.5Sr alloy in rat tibia

Abstract: Biodegradable magnesium (Mg) alloys combine the advantages of traditional metallic implants and biodegradable polymers, having high strength, low density, and a stiffness ideal for bone fracture fixation. A recently developed Mg-Ca-Sr alloy potentially possesses advantageous characteristics over other Mg alloys, such as slower degradation rates and minimal toxicity. In this study, the biocompatibility of this Mg-Ca-Sr alloy was investigated in a rat pin-placement model. Cylindrical pins were inserted in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…The gas pockets around implantable devices were observed in human patients 14 as well as animal models. 17,19,48,49 Several papers studied the effects of surface modifications on the gas pocket formation. Fischerauer et al observed decrease in the gas pocket formation in the 1st 2 weeks postimplantation with the implants treated by micro-arc oxidation, however these differences were not significant and at weeks 3 and 4 the gas volume was higher than in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas pockets around implantable devices were observed in human patients 14 as well as animal models. 17,19,48,49 Several papers studied the effects of surface modifications on the gas pocket formation. Fischerauer et al observed decrease in the gas pocket formation in the 1st 2 weeks postimplantation with the implants treated by micro-arc oxidation, however these differences were not significant and at weeks 3 and 4 the gas volume was higher than in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,18 With time the corrosion products forming around the device lower its degradation rate, however, it is highly desirable to prevent the initial corrosion burst. 12,19 More rapid degradation of Mg implant can occur during the initial period of implantation because of accumulation of body fluids around the implant due to trauma or surgery so it is important to control the H 2 gas evolution in the early period of implantation. To overcome the issue of the initial rapid corrosion and the H 2 burst leading to the formation of the gas pockets, three different strategies were used, namely, alloying, surface treatment and surface coating.…”
Section: Introductionmentioning
confidence: 99%
“…Because the results of hip arthroplasty in patients with osteonecrosis are relatively poor, much focus has been on modalities aimed at femoral head preservation (Xiaobing et al 2015 ). Thus, to succeed in establishing that, the liquid nitrogen technique, easier and convenient, was used in this study because it achieves a high success rate with reliable osteonecrosis and a short pathological process and the basic properties of the bone are maintained (Berglund et al 2016 ; Huang et al 2013 ). In this study, the ONFH was properly established with the liquid nitrogen technique used, leading to a collapse of the femoral head in the control group and restoration of the femoral with perfect osteoids formation in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A recent study showed this alloy was well tolerated by rats and the local tissue surrounding the implant, and furthermore, the healing rate paired well with the degradation rate of the alloy. 7 These results suggest the alloy may provide a stimulating environment for bone growth, which would be beneficial for applications involving bone repair.…”
Section: Introductionmentioning
confidence: 93%